Maskless and targeted creation of arrays of colour centres in diamond using focused ion beam technology. Issue 10 (31st July 2013) - Lesik, Margarita; Spinicelli, Piernicola; Pezzagna, Sébastien; Happel, Patrick; Jacques, Vincent; Salord, Olivier; Rasser, Bernard; Delobbe, Anne; Sudraud, Pierre; Tallaire, Alexandre; Meijer, Jan; Roch, Jean‐François
<x xml:space="preserve">Abstract</x> The creation of nitrogen‐vacancy (NV) centres in diamond is nowadays well controlled using nitrogen implantation and annealing. Although the high‐resolution placement of NV centres has been demonstrated using either collimation through pierced tips of an atomic force microscope (AFM) or masks with apertures made by electron beam lithography, a targeted implantation into pre‐defined structures in diamond may not be achieved using these techniques. We show that a beam of nitrogen ions can be focused to approximately 100 nm using focused ion beam (FIB) technology. The nitrogen ion beam is produced using an electron cyclotron resonance (ECR) plasma source. Combined with a scanning electron microscope, the nitrogen‐FIB offers new possibilities for the targeted creation of single defects in diamond. This maskless technology is suitable for example for the creation of optical centres in the cavities of photonic crystals or in diamond tips for scanning magnetometry.